PERANCANGAN GEDUNG SEKOLAH TAHAN GEMPA DI CABANG MUHAMMADIYAH WEDI KLATEN - Widodo, Sri; Nugroho, M.S.Priyono; Setiawan, Budi (WARTA, 2007)
Earthquake effect at  27 May 2006 have destroyed buildings ofMuhammadiyah effort in Wedi Klaten. The damages of buildings are cover:( a) TK ABA I and  II have  damages of roof and wall; ( b) TK Islamterpadu, children play group have total damage; ( c) SD Islam terpaduhave light damage. The damages of shool building have pursued theprocess of education at the school. In order to aim  recovery the damagesschool, activity of  this devotion to society is to give design of  schoolbuilding which earthquake resitance, cheap, quickly construction andcan be developed. School building designed to one class unit, so that ifneeded some classes remain to combine it, and this combining isaccomodated with area and shape of land available. Designing by usingsystem of earthquake resistance. The concepts are as light as possibleand the and the building framework which consist of column, ring beamand sloof beam are made  interaction so that forming room constructionthat having bigger moment of inertia. The activity of devotion to societyhave produced design of  one class unit with size 6m x  8 m with buildingframework consist of reinforced concrete, wall from wood and  roof madefrom waving zinc. One class unit is estimated  require  Rp.13,796,213.ofconstruction cost with duration of constructon is one month.